2016
DOI: 10.1186/s13075-016-1100-4
|View full text |Cite|
|
Sign up to set email alerts
|

Concentration of antibodies against Porphyromonas gingivalis is increased before the onset of symptoms of rheumatoid arthritis

Abstract: BackgroundThe periodontal pathogen Porphyromonas gingivalis is hypothesized to be important in rheumatoid arthritis (RA) aetiology by inducing production of anti-citrullinated protein antibodies (ACPA). We have shown that ACPA precede RA onset by years, and that anti-P. gingivalis antibody levels are elevated in RA patients. The aim of this study was to investigate whether anti-P. gingivalis antibodies pre-date symptom onset and ACPA production.MethodsA case–control study (251 cases, 198 controls) was performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 78 publications
(66 citation statements)
references
References 43 publications
(52 reference statements)
3
63
0
Order By: Relevance
“…However, we observed no association between any ACPA and these antibodies. In contrast to previous studies in 2 well‐documented Swedish cohorts, we observed no association of anti‐RgpB with CCP‐2–positive RA, nor did we observe elevated anti‐RgpB levels in RA patients compared to OA patients, or in CCP‐2–positive RA patients compared to CCP‐2–negative RA patients . Our data are consistent with previous studies showing no association of anti‐RgpB antibodies with RA or pre‐RA and no difference in anti– P gingivalis outer membrane antibody levels between RA and non‐RA cohorts .…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…However, we observed no association between any ACPA and these antibodies. In contrast to previous studies in 2 well‐documented Swedish cohorts, we observed no association of anti‐RgpB with CCP‐2–positive RA, nor did we observe elevated anti‐RgpB levels in RA patients compared to OA patients, or in CCP‐2–positive RA patients compared to CCP‐2–negative RA patients . Our data are consistent with previous studies showing no association of anti‐RgpB antibodies with RA or pre‐RA and no difference in anti– P gingivalis outer membrane antibody levels between RA and non‐RA cohorts .…”
Section: Discussionsupporting
confidence: 83%
“…Anti‐RgpB antibody levels, used as an additional marker for P gingivalis infection as in previous publications , correlated well with anti− P gingivalis antibody levels and were significantly higher in RA patients with PD than in RA patients without PD. However, we observed no association between any ACPA and these antibodies.…”
Section: Discussionsupporting
confidence: 78%
“…Instead, experimental evidence has demonstrated that this pathogen can promote autoimmune arthritis in mice through stimulation of toll-like receptor (TLR)-2 and IL-1driven Th17 response [103]. In humans, antibodies to gingipain B, a major virulence factor of P. gingivalis, are detected in samples collected before onset of symptoms of RA, supporting exposure to P. gingivalis during preclinical period [104]. However, although the presence of periodontitis was associated with progression to RA in a cohort of patients with arthralgia, this process was not linked to the presence of P. gingivalis in subgingival biofilm [105].…”
Section: Mucosal Surfaces As Sites Of Immune Amplification In Preclinmentioning
confidence: 99%
“…Unfortunately, after publication of this article [1], it was noticed that the x-axis markers for Fig. 2a and b were incorrect.…”
Section: Erratummentioning
confidence: 99%